Rancang Bangun Mesin Penggulung Tali Rafia - Rahman Fauzi; Nasrullah Nasrullah; Feidihal Feidihal; Hendra Hendra (Politeknik Negeri Padang, 2019)
Raffia rope is very popular because of its many uses, in other words it is a versatile tool. In general, raffia ropes are widely used for various matters such as business in agriculture, as a binder, as a decoration for crafts, as hangers for clothes, sewing sacks, as reinforcement materials, and many others. Raffia straps are available in the form of rolls. At this time, there are still many processes of rolling raffia still using manual methods such as direct hand rolling or using traditional methods that still use a lot of human power so that it is considered ineffective and inefficient. Because there is still a lot of traditional process of rolling the rope or using hands, the idea arises to make a raffia rope rolling machine using a motorbike and transmission. Technically appropriate technology is a bridge between traditional technology and advanced technology, therefore socio-cultural and economic aspects are also dimensions that must be taken into account in managing appropriate technology. From the desired goals, appropriate technology must apply methods that are resource-efficient, easy to maintain, and have minimal minimalistic impact. The aim of this research is to design, make and test rapia rope rollers so that they are suitable to be used to help facilitate the work of the community in the process of rolling rapia. From the results of design design. From the results of the testing obtained the tool is able to produce rolls as much as an average of 58 rolls per hour